IMPACTO TRIBUTARIO EN LAS EMPRESAS MEXICANAS DE RECICLAJE - Alegría León, Gabriel Bulmaro; Jiménez Tecillo, Francisco Javier; Tosca Magaña, Sergio Alfonso (IJRDO - Journal of Business Management, 2021)
The recycling industry in Mexico has been growing significantly as it contributes to the reduction of the amount of waste disposed of in landfills, by incineration or other means. This leads to a process for the treatment of waste, both industrial and domestic, which allows to introduce them into a production cycle of a product with the materials that compose them. For this reason, the tax authorities decided to regularize this type of industry due to the great impact it was having, since it did not have any regime with which it had to comply with its tax obligations. This led to the realization of a research where different sources have been consulted to know the tax impact on the companies dedicated to this area.